PENGEMBANGAN KONSEP ECOTOURISM PADA SENDANG DESA TEKERHARJO, KECAMATAN SOLOKURO, KABUPATEN LAMONGAN - Hammam Rofiqi Agustapraja (Jurnal Teknika, 2019)
Economic inequality between cities and villages, this must be immediately prevented and minimized because it is an injustice in the economic field, therefore the government through village funds encourages villages to develop their existing potential, one of them is from the tourism sector, Takerharjo Village sees potential spring and spring as something more value that must be lifted and highlighted as an icon of a new tourist place managed by the village, it requires good planning, this study aims to provide recommendations on the Sendang arrangement concept in the village by using the concept of Ecotourism to plan the potential of spring and Takerharjo village springs became a village tourism icon, and also held a socialization on the importance of preserving the natural environment of the area so that the spring water source was maintained, with the aim that the spring and springs of Takerharjo Village could improve the welfare of the Takerharjo Village community.